Perencanaan Arsitektur Teknologi Informasi Kelurahan Babau Menggunakan TOGAF ADM - Yohanes Hugo Maur; Andi Wahju Rahardjo Emanuel (Universitas Atma Jaya Yogyakarta, 2021)
Abstract. Information technology architecture planning for Baubau Village using TOGAF ADM. Babau Village is a village located in Kupang Regency, East Nusa Tenggara Province. Currently, Babau Village has implemented information technology as a centre for information and administrative services. To improve the quality of service to the community, existing information technology needs to be further developed because the amount of information in the system will continue to increase along with population growth. The problem faced if information technology is not developed is a system performance problem. For further development to be more focused, research on an information technology architecture design for Babau Village. The design using TOGAF ADM is a blueprint and a roadmap for the development of advanced information technology services. The aim is that the existing business processes within the Babau Village related to information and administrative services continue to develop according to the needs of the community and the organizational management of Babau Village.Keywords: enterprise architecture planning, TOGAF, ADM, Babau VillageAbstrak. Kelurahan Babau adalah sebuah kelurahan yang terletak di Kabupaten Kupang, Provinsi Nusa Tenggara Timur. Saat ini Kelurahan Babau sudah menerapkan teknologi informasi sebagai pusat pelayanan informasi dan administrasi. Demi meningkatkan kualitas pelayanan kepada masyarakat, teknologi informasi yang ada perlu dikembangkan lebih lanjut karena jumlah informasi yang ada dalam sistem akan terus meningkat seiring pertumbuhan jumlah penduduk. Masalah yang dihadapi apabila teknologi informasi tidak dikembangkan ialah masalah kinerja sistem. Agar pengembangan tahap lanjut lebih terarah, penelitian mengenai sebuah perancangan arsitektur teknologi informasi untuk Kelurahan Babau. Perancangan yang menggunakan TOGAF ADM tersebut merupakan blueprint dan juga roadmap untuk pengembangan pelayanan teknologi informasi tahap lanjut. Tujuannya ialah proses bisnis yang ada didalam Kelurahan Babau terkait pelayanan informasi dan administrasi terus berkembang sesuai dengan kebutuhan masyarakat dan pengurus organisasi Kelurahan Babau.Kata Kunci: arsitektur teknologi informasi, TOGAF, ADM, Kelurahan Babau